VD_FINDINFO HC / 2014 / 87 vom 7. Januar 2014 - VD Tribunal cantonal (2014)
AGENT D'AFFAIRES, HONORAIRES, HONORAIRES CALCULÉS EN FONCTION DU RÉSULTAT POSITIF, MODÉRATION | 7 LPAg, 9 al. 3 LPAg, 95 LPA-VD, 98 LPA-VD